2019
DOI: 10.3389/fnhum.2019.00012
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomical and Neurochemical Correlates of Parental Verbal Abuse: A Combined MRS—Diffusion MRI Study

Abstract: Despite the critical impact of parental dialog on children who remain physically and psychologically dependent, most studies have focused on brain alterations in people exposed to moderate-to-high levels of emotional maltreatment with/without psychopathology. We measured metabolites in the pregenual anterior cingulate cortex (pgACC) acquired with single-voxel proton magnetic resonance spectroscopy and anatomical connectivity assessed with probabilistic tractography in 46 healthy young adults who experienced no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
(126 reference statements)
1
8
0
Order By: Relevance
“…the uncinate fasciculus [UF]) were also confirmed in several studies (McCarthy‐Jones et al., 2018 ; Meinert et al., 2019 ; Ohashi et al., 2017 ). Four recent studies confirmed structural changes in the cingulum or in fibers connecting the cingulum with other brain regions (Kim, et al., 2019 ; McCarthy‐Jones et al., 2018 ; Meinert et al., 2019 ; Tendolkar et al., 2018 ), and in the CC (Jensen et al., 2018 ; Lim et al., 2019 ; McCarthy‐Jones et al., 2018 ; Meinert et al., 2019 ). Only one study so far confirmed a relation between childhood maltreatment and hippocampal projections (McCarthy‐Jones et al., 2018 ).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…the uncinate fasciculus [UF]) were also confirmed in several studies (McCarthy‐Jones et al., 2018 ; Meinert et al., 2019 ; Ohashi et al., 2017 ). Four recent studies confirmed structural changes in the cingulum or in fibers connecting the cingulum with other brain regions (Kim, et al., 2019 ; McCarthy‐Jones et al., 2018 ; Meinert et al., 2019 ; Tendolkar et al., 2018 ), and in the CC (Jensen et al., 2018 ; Lim et al., 2019 ; McCarthy‐Jones et al., 2018 ; Meinert et al., 2019 ). Only one study so far confirmed a relation between childhood maltreatment and hippocampal projections (McCarthy‐Jones et al., 2018 ).…”
Section: Introductionmentioning
confidence: 78%
“…graduation of severity) in similar populations of healthy young adults have reported widespread associations between maltreatment and white matter integrity (e.g. Hanson et al., 2015 ; Jensen et al., 2018 ; Kim, et al., 2019 ; McCarthy‐Jones et al., 2018 ; Ohashi et al., 2017 ; Tendolkar et al., 2018 ) and several of these studies looked at similar types and levels of abuse and neglect as in the study reported here (e.g. Hanson et al., 2015 ; McCarthy‐Jones et al., 2018 ; Tendolkar et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the generalized dice similarity coefficient as a measure of overlap was computed from the intersection and union of VOIs (Kim et al, 2019;Park et al, 2018). We used the Shen brain atlas (Shen et al, 2013), which consists of 268 regions of interest, including the AIC and mPFC.…”
Section: Anatomical Consistency Among Participants' Voismentioning
confidence: 99%
“…Functional impairments during this period appear to persist for a substantial time after the remission of depression 5,6 . In addition, emotional adversities experienced before young adulthood cause structural [7][8][9] , functional 10,11 , and neurochemical 12 alterations in the brain. Therefore, various variables consisting of trans-diagnostic symptoms, related behavioral patterns, and current and past stresses may be intricately intertwined in young adulthood depression.…”
Section: Introductionmentioning
confidence: 99%